Efficacy and safety of low dose Mycophenolate mofetil treatment for immunoglobulin G4-related disease: a randomized clinical trial. (14th August 2018) - Yunyun, Fei; Yu, Peng; Panpan, Zhang; Xia, Zhang; Linyi, Peng; Jiaxin, Zhou; Li, Zhang; Shangzhu, Zhang; Jinjing, Liu; Di, Wu; Yamin, Lai; Xiaowei, Liu; et al.
Abstract: Objectives: This randomized, controlled clinical trial aims to compare the efficacy and safety of glucocorticoid combined with MMF and glucocorticoid monotherapy for patients with IgG4-related disease. Methods: Sixty-nine patients newly diagnosed with IgG4-related disease were randomly divided into two groups (35 patients in Group I and 34 patients in Group II). Patients in Group I received glucocorticoid monotherapy (0.6–0.8 mg/(kg·day) and tapered gradually); patients in Group II received glucocorticoid combined with MMF therapy (1–1.5 g/day). All the patients were followed up at 1, 3, 6 and 12 months. The primary endpoint was response rate in 12 months and the secondary endpoints were relapse, remission rate and adverse reactions. Results: Group I and Group II shared almost the same efficacy at the 1 month treatment, but during the follow-up, the complete response rate in Group II was much higher than that in Group I at different time points, and the cumulative relapse rate during 1 year of therapy was much higher in Group I than that in Group II (40.00 vs 20.59%). The remission rate was lower in Group I (51.42 vs 76.47%). Relapses were more likely to happen in lung, lacrimal gland, salivary gland, paranasal sinus and kidney. MMF could reduce relapse, especially organs recurrence. No serious adverse reactions occurred in the two groups. Conclusion: Combination treatment with glucocorticoid and MMF was more effective than the monotherapy, and the relapse of IgG4-related disease might be associated with the elevated levels of serum IgG4 and the low glucocorticoid maintenance dose. Trial registration: ClinicalTrials.gov, www.clinicaltrials.gov, NCT02458196.